Extraction and Identification of Dye from Walnut Green Husks for Silk Dyeing - Mirjalili, Mohammad; Nazarpoor, Khosro; Karimi, Loghman (Asian Journal of Chemistry, 2010)
This paper introduces an analytical method for identifying the colour base extracted from the walnut shell (Juglans regia L.) which is based on the extraction of colourant from walnut shell through a solvent using Soxhlet apparatus. Here, the main colour bases of samples were isolated and analyzed by column chromatography, thin layer chromatography, infrared, nuclear magnetic resonance and mass spectrometry. The method easily allows the identification of several colour bases by detecting the molecular structure and finally the separation of chemical structures from this plant. The absorbability of the extracted dye using ethanol solvent has been compared to that of the dye from the raw plant in order to determine the dyeing efficiency rate through dyeing silk fibers. The results show that the exhaustion rate for the extracted dye increases by 54 % compared to the raw dye. This per self leads to a considerable decrease in the amount of the extracted dye used to reach the same desired results.